Hadith of Women Leadership in the Qira'ah Mubadalah Approach - Ziyan Yusriana Asri; Indal Abror (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Hadith become the source of both law in Islam, where textual and contextual application is used. Some hadith needed editors of the qur’an texts to get an understanding of the hadiths being studied. In this study, we adopted one hadiths which is still a public debate. The focus of this research is that of women’s leadership gifts to be studied by Mubadalah methods the one that was championed by Faqihuddin Abdul Qadir. Footsteps his research was to throne the hadith and to explain the terms and then apply traditional thought Mubadalah as a step to gaining an understanding of the hadith which did not affect women’s subornation anymore. Further explaining the roles that women have performed in public space the study concludes that basic Islamic principle used in the hadith is surah An-Nisa verse 59 and the surah at-taubah verse 71. In both the verse explained the reprisals for those who had faith and obedience to their leaders. Then the main idea when discovered applies the mubadalah method is either the lack of luck or luck a victory for nation. And the final step is to enter the subject which is there is no mention (men). Men could’ve done damage if he’d been a leader. The understanding given by the mubadalah method is how to make a hadith impression at all parties, not only one participant and costs other by using the passage of the qur’an as understanding.